COMPREHENSIVE STRATEGIES FOR REDUCING UNEMPLOYMENT IN THE MODERN GLOBAL ECONOMY - Raximov Baxromjon Ibrohimovich,; Abdullajonov Murodjon Saydullo o’g’li, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
ANNOTATION: This scientific article provides a multidimensional analysis of the key strategies for reducing unemployment in the context of contemporary global economic challenges. Unemployment is examined not merely as a statistical indicator but  as  a  complex  systemic  phenomenon  with  profound  impacts  on  social  stability, human capital development, and long-term national security. The work explores the primary  causes of  modern unemployment,  including technological  shifts, structural economic changes, and the skills mismatch. It offers a detailed examination of core solutions:  reforming  education  systems  to  align  with  labor  market  demands, developing large-scale vocational retraining and lifelong learning programs, fostering entrepreneurship  and  small  business  ecosystems,  adapting  to  the  digital  economy, addressing  specific  youth  employment  challenges,  and  analyzing  successful international  models  from  Scandinavia,  Germany,  and  East  Asia.  The  conclusion synthesizes  the  findings  into  a  coherent  framework  for  policy,  emphasizing  the necessity  of  an  integrated,  proactive,  and  multi-stakeholder  approach  to  creating sustainable employment in a rapidly evolving world.